Faktor-Faktor Yang Mempengaruhi Tax Avoidance Perusahaan Pertambangan - Hanum Fatikha Rakhmawati; Aisyaturrahmi Aisyaturrahmi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the factors that influence tax avoidance in mining companies listed on the Indonesia Stock Exchange for the period 2021–2023. These factors include corporate governance (independent commissioners, audit committees, and managerial ownership), company performance (leverage and profitability) and corporate social responsibility (CSR) disclosure. This study uses a quantitative approach with secondary data in the form of annual reports and company sustainability reports. Data analysis uses panel data regression analysis with Stata software version 17. The results of the study show that profitability has a positive effect on tax avoidance. Meanwhile, corporate governance, leverage, and CSR disclosure have no effect. This finding indicates that company profitability can be an important indicator of tax avoidance tendencies. Therefore, these results can be used as a consideration for tax authorities in improving supervision, as well as for company management in implementing more responsible tax policies.